Environmental transformations and ecological effects of iron-based nanoparticles. (January 2018) - Lei, Cheng; Sun, Yuqing; Tsang, Daniel C.W.; Lin, Daohui
Abstract: The increasing application of iron-based nanoparticles (NPs), especially high concentrations of zero-valent iron nanoparticles (nZVI), has raised concerns regarding their environmental behavior and potential ecological effects. In the environment, iron-based NPs undergo physical, chemical, and/or biological transformations as influenced by environmental factors such as pH, ions, dissolved oxygen, natural organic matter (NOM), and biotas. This review presents recent research advances on environmental transformations of iron-based NPs, and articulates their relationships with the observed toxicities. The type and extent of physical, chemical, and biological transformations, including aggregation, oxidation, and bio-reduction, depend on the properties of NPs and the receiving environment. Toxicities of iron-based NPs to bacteria, algae, fish, and plants are increasingly observed, which are evaluated with a particular focus on the underlying mechanisms. The toxicity of iron-based NPs is a function of their properties, tolerance of test organisms, and environmental conditions. Oxidative stress induced by reactive oxygen species is considered as the primary toxic mechanism of iron-based NPs. Factors influencing the toxicity of iron-based NPs are addressed and environmental transformations play a significant role, for example, surface oxidation or coating by NOM generally lowers the toxicity of nZVI. Research gaps and future directions are suggested with an aim to boost concerted research efforts on environmental transformations and toxicity of iron-based NPs, e.g., toxicity studies of transformed NPs in field, expansion of toxicity endpoints, and roles of laden contaminants and surface coating. This review will enhance our understanding of potential risks of iron-based NPs and proper uses of environmentally benign NPs. Graphical abstract: Highlights: Transformations of iron-based NPs are greatly affected by environmental conditions. Toxic mechanisms are correlated to transformations of iron-based NPs. Factors influencing the toxicity and impacts on various organisms are highlighted. Future directions on transformation and toxicity of iron-based NPs are proposed. Abstract : Environmental transformations of iron-based NPs regulate their eco-toxicities.